A poet's “last days' writings” (Osip Mandelstam's poetry written in May – July 1937) (Филологический класс, 2011)
The article explores the phenomenon of “the last day” of a poet through the poems written by Osip Mandelstam after his return from the exile in Voronezh. The researcher analyses the subject organization of the poems and the nature of their addressing patterns (the external addressee, Lilya Popova). The researcher comments on the details that reveal the specific features of the 1930s, and exhibits the entire range of the Poet's dramatic experiences and emotions.